Anterior Cervical Discectomy and Fusion YouTube Videos as a Source of Patient Education - Ovenden, Christopher Dillon (Asian Spine J, 2018)
STUDY DESIGN: Cross sectional study. PURPOSE: To assess the quality of anterior cervical discectomy and fusion (ACDF) videos available on YouTube and identify factors associated with video quality. OVERVIEW OF LITERATURE: Patients commonly use the internet as a source of information regarding their surgeries. However, there is currently limited information regarding the quality of online videos about ACDF. METHODS: A search was performed on YouTube using the phrase ‘anterior cervical discectomy and fusion.’ The Journal of the American Medical Association (JAMA), DISCERN, and Health on the Net (HON) systems were used to rate the first 50 videos obtained. Information about each video was collected, including number of views, duration since the video was posted, percentage positivity (defined as number of likes the video received, divided by the total number of likes or dislikes of that video), number of comments, and the author of the video. Relationships between video quality and these factors were investigated. RESULTS: The average number of views for each video was 96,239. The most common videos were those published by surgeons and those containing patient testimonies. Overall, the video quality was poor, with mean scores of 1.78/5 using the DISCERN criteria, 1.63/4 using the JAMA criteria, and 1.96/8 using the HON criteria. Surgeon authors’ videos scored higher than patient testimony videos when reviewed using the HON or JAMA systems. However, no other factors were found to be associated with video quality. CONCLUSIONS: The quality of ACDF videos on YouTube is low, with the majority of videos produced by unreliable sources. Therefore, these YouTube videos should not be recommended as patient education tools for ACDF.